A Questionnaire on Relative Deprivation of University Students and Its Application in Measuring Mental Health - Jia, Liuzhan (Frontiers in Psychology, 2022)
Objective: Relative deprivation is associated with collective and individual variables in psychology. But so far, there are few studies on measuring university students’ relative deprivation. So this study designs USRDQ (University Students’ Relative Deprivation Questionnaire) and verifies its validity and reliability, then uses it to measure students’ mental health. Methods: After reviewing relevant studies, conducting theoretical analysis and conducting an open questionnaire survey, this paper determined USRDQ’s structural dimension. A total of 103 university students were selected to take the open questionnaire survey, 200 were selected to engage in the item analysis, exploratory factor analysis, and internal consistency reliability test, 257 were selected to engage in the confirmatory factor analysis, and another 287 were selected to take the retest reliability. Results: USRDQ includes 19 items under three dimensions: social comparison, cognitive evaluation and emotional experience. Factor loads range from 0.49 to 0.87, which accounted for 63.39% of the total variation. The questionnaire has good fitting indicators(2/df=2.64,NFI=0.89,CFI=0.93, GFI=0.91, RMSEA=0.08). The Cronbach α coefficient of the questionnaire is 0.916 and the coefficients of three factors range from 0.805 to 0.934. The results of the survey show that student’s relative deprivation is quite high with a mean of 76.78, and a standard deviation of 16.96.